12p deletion spectrum syndrome: a new case report reinforces the evidence regarding the potential relationship to autism spectrum disorder and related developmental impairments. Issue 1 (December 2016) - Leyser, Marcio; Dias, Bruno; Coelho, Ana; Vasconcelos, Marcio; Nascimento, Osvaldo
Abstract Background Autism Spectrum Disorders (ASD) now encompass a broad heterogeneous group of people who present in the early developmental years with a wide range of social and communication deficits, which are typically also associated with complex repetitive behaviors and circumscribed interests. The target goal is to heighten readers' perception into the trend to personalize the distinct autistic and related developmental conditions encompassing the 12p region. Case Presentation This is a case-report of a 4-year-old male who presented the core signs of ASD, which were thought to be related to a rare 12p13.2 deletion. We further reviewed the literature in order to outline the related developmental conditions in the 12p region. Aside from this patient reported here, we found an additional number of 43 cases described in the medical literature since 1974, that have been related to deletions in the 12p region. However, to the best of our knowledge, none of the previous had been specifically linked to the 12p13.2 band. Conclusions The 12p deletion spectrum is rarely described as part of the selective genotypes thought to be related to ASD. Even inside of a small piece of the puzzle, there might be ample variation in the behavioral and clinical phenotypes of children and adults presenting with this particular genetic profile. In that regard, the particular 12p13.2 distal deletion presentation is one of the possible genotypes encompassed by the "12p deletion spectrum syndrome", that might be potentially connected to the diagnosis of ASD and related developmental disorders.